2002
DOI: 10.1016/s0925-4439(01)00101-6
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent activation of cell cycle and apoptosis mechanisms in the right ventricle by pressure overload

Abstract: The molecular basis of the intrinsic vulnerability of the compliant right ventricle to chronic pressure overload is poorly understood. Extensive apoptosis, possibly coupled with aberrant cell cycle reentry, in response to unrestrained biomechanical stress may account for this phenotypic flaw. To address this issue we have studied changes in expression of the cell cycle and apoptosis regulators in the right ventricle following induction of pulmonary hypertension in the rat by injection of monocrotaline. Hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…We found that apoptosis started early and declined when clinically manifest RV failure occurred. This finding is consistent with other pressure-overload mediated RV disease studies (11,12).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that apoptosis started early and declined when clinically manifest RV failure occurred. This finding is consistent with other pressure-overload mediated RV disease studies (11,12).…”
Section: Discussionsupporting
confidence: 93%
“…Apoptosis and fibrosis have been shown to act in isolation or in concert to reduce LV performance (9,10). In contrast, the association of apoptosis with RV disease progression (11,12) is unclear. Recently, in vivo imaging of cardiac apoptosis with 99m Tc-annexin V ( 99m Tc-annexin) was proven feasible, because 99m Tc-annexin binds to exposed phosphatidylserine on the outer surface of apoptotic cells (13).…”
mentioning
confidence: 99%
“…There are evidences suggesting that cell cycle and apoptosis pathways are co-activated in pressure-overload RV in MCT model [5]. In this sequence, we assessed the LV myocardial apoptosis, and found increased rates of apoptosis both in MCT-4 and MCT-6.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)mentioning
confidence: 89%
“…It is also worth noting that high levels of the antiapoptotic protein Bcl2 have been found in early stages of hypertrophy (67) and that arterial wall thickness, perivascular fibrosis, and cardiac hypertrophy induced by angiotensin II treatment are significantly reduced in Ets-1-deficient mice (68).…”
Section: Discussionmentioning
confidence: 99%